THE RELATIONSHIP BETWEEN WNT (WINGLESS/INT) PATHWAYS REACTIVE OXYGEN SPECIES (ROS) AND CANCER - Fitriannisa F. Zubaidi (Fakultas Kedokteran Universitas Islam Al-Azhar, 2018)
Reactive oxygen species has been known to play a role in the formation of cancer and determination of cellular death. Less known, however, is its more recently studied role in regulating cellular physiologic functions. The mechanism of how ROS switches between these roles involves detailed interactions with different pathways. The Wnt pathway, specifically the canonical Wnt/β-catenin pathway, seems to be one that has this role switching effect, depending on the amount of ROS present in the cellular microenvirent. This review aims to revisit the regulation of ROS levels, their relationship to cancer, and how the Wnt pathways influence the effect of ROS.